2009
DOI: 10.1007/bf03178317
|View full text |Cite
|
Sign up to set email alerts
|

Characterization and selection ofBacillus sp. strains, effective biocontrol agents againstFusarium oxysporum f. sp.radicis-lycopersici, the causal agent of Fusarium crown and root rot in tomato

Abstract: -The antagonistic activities of 20 Bacillus isolates were tested with dual culture and greenhouse conditions against Fusarium oxysporum f. sp. radicis-lycopersici (FORL) race 0, the causal agent of Fusarium crown and root rot of tomato. Under dual culture, 10 isolates inhibited mycelial growth > 38% and the most effective inhibited fungal growth > 50%. The 20 Bacillus isolates were tested for production of volatiles, cyanide, antibiotics, and phosphorus solubilisation; 15 isolates produced volatiles that inhib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 41 publications
0
12
1
Order By: Relevance
“…Several Bacillus species have demonstrated antifungal activity against fungal phytopathogens, including B. cinerea and/or Fusarium species, in vitro [39][40][41][42][43]. However, antifungal capability is a function of bacterial strain and fungal pathogen.…”
Section: Bacillus Speciesmentioning
confidence: 99%
See 1 more Smart Citation
“…Several Bacillus species have demonstrated antifungal activity against fungal phytopathogens, including B. cinerea and/or Fusarium species, in vitro [39][40][41][42][43]. However, antifungal capability is a function of bacterial strain and fungal pathogen.…”
Section: Bacillus Speciesmentioning
confidence: 99%
“…The application of Bacillus species pre-harvest reduced the incidence and severity of diseases caused by F. oxysporum [42], Alternaria solani, and Phytophthora infestans [44] on tomato plants and B. cinerea fruit rot on strawberry plants [29]. Postharvest application of Bacillus species has also caused fungal suppression; decay was reduced on pears, tomatoes, bananas, and oranges [12,31,32,45].…”
Section: Bacillus Speciesmentioning
confidence: 99%
“…Some authors found that production of pyoverdines contributes to the bio-control capacity of the fluorescent Pseudomonas. Conversely, other studies failed to establish a link between production of pyoverdine and antagonism against phytopathogenic fungi Kumar et al,2008;Saidi et al, 2009;Yang et al, 2009. Pseudomonas spp. has been shown to produce siderophores able to chelate any available iron (Henry et al, 1991).…”
Section: Introductionmentioning
confidence: 99%
“…The development of biological controls has recently received attention because of their economic and ecological advantages, as well as political demands. Several studies have examined biological control approaches against the disease (6, 28, 31, 35). In Japan, Iwamoto and Aino (20) reported that a commercial biocontrol agent (an endophytic bacterium of tomato roots, Pseudomonas fluorescens FPH9601) significantly suppressed the disease in tomato fields, although the sale of the agent is currently suspended.…”
mentioning
confidence: 99%